\(\sqrt{\left(x-1\right)\left(x-5\right)}-3\sqrt{1-x}=0\)
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

21 tháng 11 2015

a= - 4 . a2 + a = 12

21 tháng 11 2015

ta có \(\sqrt{\left(x-1\right)\left(x-5\right)}-3\sqrt{1-x}=0\)

\(\Leftrightarrow\sqrt{\left(1-x\right)\left(5-x\right)}-3\sqrt{1-x}=0\)

\(\Leftrightarrow\sqrt{1-x}\left(\sqrt{5-x}-3\right)=0\) 

mà x<1=>x khác 1=>\(\sqrt{5-x}-3=0\)

\(\Rightarrow x=-4\)=> \(a^2+a=12\)

4 tháng 4 2017

a) Phương trình 1,5x2 – 1,6x + 0,1 = 0

Có a + b + c = 1,5 – 1,6 + 0,1 = 0 nên x1 = 1; x2 = \(\dfrac{0,1}{15}\)

c) \(\left(2-\sqrt{3}\right)x^2+2\sqrt{3x}-\left(2+\sqrt{3}\right)=0\)

\(a+b+c=2-\sqrt{3}+2\sqrt{3}-\left(2+\sqrt{3}\right)=0\)

Nên x1 = 1, x2 = \(\dfrac{-\left(2+\sqrt{3}\right)}{2-\sqrt{3}}\) = -(2 + \(\sqrt{3}\))2 = -7 - 4\(\sqrt{3}\)

d) (m – 1)x2 – (2m + 3)x + m + 4 = 0

Có a + b + c = m – 1 – (2m + 3) + m + 4 = 0

Nên x1 = 1, x2 = \(\dfrac{m+4}{m-1}\)

4 tháng 4 2017

a) Phương trình 1,5x2 – 1,6x + 0,1 = 0

Có a + b + c = 1,5 – 1,6 + 0,1 = 0 nên x1 = 1; x2 =

b) Phương trình √3x2 – (1 - √3)x – 1 = 0

Có a – b + c = √3 + (1 - √3) + (-1) = 0 nên x1 = -1, x2 = =

c) (2 - √3)x2 + 2√3x – (2 + √3) = 0

Có a + b + c = 2 - √3 + 2√3 – (2 + √3) = 0

Nên x1 = 1, x2 = = -(2 + √3)2 = -7 - 4√3

d) (m – 1)x2 – (2m + 3)x + m + 4 = 0

Có a + b + c = m – 1 – (2m + 3) + m + 4 = 0

Nên x1 = 1, x2 =

17 tháng 8 2018

\(A=\left(x-2\right)\cdot\sqrt{\dfrac{9}{\left(x-2\right)^2}}+3=\dfrac{3\left(x-2\right)}{\left|x-2\right|}+3=\dfrac{3\left(x-2\right)}{-\left(x-2\right)}=-3+3=0\)

\(B=\sqrt{\dfrac{a}{6}}+\sqrt{\dfrac{2a}{3}}+\sqrt{\dfrac{3a}{2}}=\dfrac{\sqrt{a}}{\sqrt{6}}+\dfrac{\sqrt{2a}}{\sqrt{3}}+\dfrac{\sqrt{3a}}{\sqrt{2}}=\dfrac{\sqrt{a}+2\sqrt{a}+3\sqrt{a}}{\sqrt{6}}=\dfrac{6\sqrt{a}}{\sqrt{6}}=\sqrt{6a}\)

\(E=\sqrt{9a^2}+\sqrt{4a^2}+\sqrt{\left(1-a\right)^2}+\sqrt{16a^2}=3\left|a\right|+2\left|a\right|+\left|1-a\right|+4\left|a\right|=9\left|a\right|+1-a=-9a+1-a=-10a+1\)

\(F=\left|x-2\right|\cdot\dfrac{\sqrt{x^2}}{x}=\left|x-2\right|\cdot\dfrac{\left|x\right|}{x}=\dfrac{x\left(x-2\right)}{x}=x-2\)

\(H=\dfrac{x^2+2\sqrt{3}\cdot x+3}{x^2-3}=\dfrac{\left(x+\sqrt{3}\right)^2}{\left(x-\sqrt{3}\right)\left(x+\sqrt{3}\right)}=\dfrac{x+\sqrt{3}}{x-\sqrt{3}}\)

\(I=\left|x-\sqrt{\left(x-1\right)^2}\right|-2x=\left|x-\left(-\left(x-1\right)\right)\right|-2x=\left|x+x-1\right|-2x=\left|2x-1\right|-2x=1-4x\)